Nitrogen reducing mechanism by microporous aeration based on microbial population characteristics water temperature factor - Lu, Cheng (Environmental technology, 2024)
The formation of black odour water is primarily attributed to the elevated concentration of organic pollutants, along with an excessive amount of nitrogen and phosphorus, ultimately leading to an anoxic aquatic environment. The water temperature influence mechanism on black-odorous water restoration by microporous aeration is still lacking depth study. This paper selected (15-18) ℃ (spring and autumn), (22-25) ℃ (summer), (8-11) ℃ (winter) as temperature conditions, and investigated temperature influence on nitrogen reduction. Researches showed that: (1) The removal rates of COD, NH4+-N and TN were significantly positively correlated with temperature (r = 0.99, 0.96, 0.97), the lowest removal rates were 83.16%, 95.68%, 58.7% ((8-11) ℃), the highest values were 92.67%, 98.27%, 70.96% ((22-25) ℃), respectively. (2) At a temperature range of 22-25°C, the microbial community exhibited the highest levels of abundance, diversity, and uniformity. Notably, Proteobacteria dominated this temperature range with a relative abundance of 79.72%. Furthermore, temperature positively correlated with the majority of dominant bacterial species, suggesting that conditions at 22-25°C are highly conducive to the growth of most bacterial communities. Among these, Limnohabitans, Alsobacter, and Candidatus_Aquirestis, which possess key functions in denitrification and nitrogen removal, displayed significantly higher abundances. It explains the positive correlation between temperature and removal rates of COD, TN and NH4+-N from microbial population's perspective. Thus, the best temperature for repairing black-smelly water is (22-25) ℃. This study provides technical reference for mechanism research and practical application of microporous aeration